Spiritual and personal approach in research of spiritual self-realization of future psychologist in the educational socialization - Г. Лаптєва (Київський національний університет імені Тараса Шевченка, 2015)
This article analyzes the contemporary spiritual and personal approach in psychological science. Attention is paid to the disclosure of this approach in the psychology of spirituality and its subsequent application in the study of problems of spiritual self-realization the psychologists of the future in terms of education and socialization. Under the spiritual and personal approach is considered a set of conceptual ideas, principles, models and techniques which in turn contribute to a more objective understanding of students during their disclosure spiritual potential. We consider the structural component composition spiritual and personal approach (conceptual, psychodiagnostical, psychological, educational, advisory). Analyze the key principles of spiritual and personal approach (spiritual and personal integration, the principle of hierarchy (authority) and the principle of value-semantic determination). We note that the self-realization of the spiritual potential of the individual is a manifestation of spiritual creativity (inner world), which requires the conscious self, the development potential of human capabilities, making an impact on others, to their own fate, to the world at large. Age-related features make students particularly sensitive period in the formation of future professional orientation, especially spiritually oriented activities. We consider the importance of organization training of future specialists in universities, largely depends on which direction will take valuable motivational and filling their spiritual and professional activities in the future.

Стаття присвячена аналізу сучасного духовно-особистісному підходу у психологічній науці. Увага приділяється розкриттю даного підходу у психології духовності та з подальшим його застосуванням у дослідженні проблеми духовної самореалізації майбутніх психологів в умовах освітньої соціалізації. Під духовно-особистісним підходом розглядається сукупність концептуальних уявлень, принципів, моделей і методів, які в свою чергу сприяють більш об'єктивному розумінню особистості студента у процесі розкриття духовного потенціалу. Вікові особливості роблять студентство особливо чутливим періодом до формування спрямованості особистості майбутнього професіонала, особливо духовно спрямованої діяльності. Розглядається важливість організованості підготовки майбутніх фахівців у ВНЗ, значною мірою залежить, якої спрямованості набуде мотиваційно-ціннісне наповнення їхньої духовної та професійної діяльності в майбутньому.
Духовно-особистісний підхід в дослідженні духовної самореалізації майбутніх психологів в умовах освітньої соціалізації
Keywords: духовно-особистісний підхід; духовна самореалізація; духовний потенціал; майбутні психологи; spiritual and personal approach; spiritual self-realization; spiritual potential; future psychologists